Testing Small Ruminants for Mastitis Using the California Mastitis Test (CMT) and How to Properly Hand-Milk Goats - Izabella Toledo; Justina Jade Dacey (EDIS)
This publication provides two step-by-step guides: one for testing small ruminants for mastitis using the CMT, and another for hand-milking goats. Written by Izabella Toledo and Justina Dacey, and published by the UF/IFAS Department of Animal Sciences, February 2022.